Analysis of the Influence of Negative Media Exposure and Product Quality on Brand Trust: A Case Study of the Honda Brand - Rahmasari, Vita; Hidayat, Amri Syarif (University of Darussalam Gontor, 2024)
This study aims to examine the effects of negative media exposure related to the eSAF frame corrosion case on Honda motorcycles and product quality on consumer trust in the Honda brand. A quantitative research method with a survey approach was employed. The research sample comprised Honda motorcycle consumers in Klaten. Data were analyzed using multiple linear regression analysis. The results indicated that negative media exposure related to the eSAF frame case did not significantly affect consumer trust in the Honda brand. In contrast, product quality demonstrated a positive and significant effect on consumer trust. This suggests that consumers tend to prioritize the overall quality of the product over focusing solely on a single negative issue.This study offers important implications for companies in managing crisis communication and maintaining consumer trust.